أبعاد الأسلوب اللغوي في السرد القرآني: دراسة أسلوبية لقصص النبي عيسى عليه السلام - Sodikin; Murtadho, Muhammad Alfa Choirul (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
Abstract: Al-Qur'an, as the greatest miracle granted to Prophet Muhammad (PBUH), stands out due to its two fundamental aspects: its profound, wisdom and its unparalleled linguistic eloquence. Among its many narratives, the story of Prophet Isa and his mother, Maryam, appears in multiple surahs, offering rich insights into human history. In this regard, stylistics, as a branch of linguistic studies, plays a pivotal role in deciphering the text’s deeper meanings, messages, and authorial intent, ultimately enriching a richer the reader’s comprehension. This study employs a qualitative descriptive approach, utilizing listening and note-taking techniques for data collection. The findings indicate that the Qur'an employs a diverse range of stylistic features in narrating the story of Prophet Isa, including: (1) variations in word choice, encompassing formal, informal, and conversational styles; (2) tonal distinctions, where formal, informal, and conversational tones are evident; and (3) sentence structures that incorporate rhetorical techniques such as climax, anticlimax, and repetition to strengthen the narrative’s impact.